Scaling up agricultural adaptation through insurance: Bringing together insurance, big data and agricultural innovation - Hellin, Jonathan; Hansen, James W.; Rose, Alison; Braun, Mélody (2017)
Our belief that index insurance holds significant potential to reduce climate risk for small-holder farmers through its protection and promotion roles, significantly improving the welfare of farm households, is why we are bringing together experts from across the insurance, agriculture and climate change sectors to find the best ways to scale-up index insurance schemes as a key climate change adaptation action. This background paper includes a short introduction to index-based agricultural insurance. The bulk of the paper (Section 3), however, focuses on the challenges and opportunities to scaling up agricultural adaptation through insurance. Based on a review of secondary literature, interviews with key informants and the authors’ experience, we highlight a number of issues that warrant concerted multi-stakeholder attention and action in order to realize the potential of index insurance as a key component of climate change adaptation.